French Theater and the Memory of the Great War - Susan McCready (Studies in 20th & 21st Century Literature, 2017)
A systematic examination of the ground on which French-language playwrights chose to stage their confrontation with the war would expose many of the literary and cultural biases on which our collective memory of the Great War is based. Even the brief outline of French-language war plays provided in this essay challenges many of our most cherished assumptions about war experience and the meaning of the Great War.
Keywords: theater; drama; modernism; naturalism; memory; commemoration